2012
DOI: 10.1002/ajhb.22282
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between inverted body mass index and body mass index as proxies for body fatness and risk factors for metabolic risk and cardiorespiratory fitness in portuguese adolescents

Abstract: Objectives: To compare inverted body mass index (iBMI, cm2/kg) and body mass index (BMI, kg/m2) as predictors of body fatness, metabolic risk, and cardiovascular fitness in adolescents. Methods: A cross‐sectional school‐based study was conducted on 445 Portuguese adolescents (252 girls and 193 boys) aged 10–17 years. Height and body mass were assessed to determine iBMI and BMI, percent body fatness was determined from skinfold measures (tricep, subscapular) using the Slaughter et al. (1988: Hum Biol 60: 709–72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the present study, however, the tracking of each skinfold and of skinfold-based body fat was correlated to that of BMI, thus not invalidating the use of BMI when analyzing the tracking of adiposity in children. Together with BMI, we analyzed the iBMI, because this index was suggested to be more biologically sound than the BMI and to represent a better proxy of fat mass [33]. However, we observed no substantial difference between BMI and iBMI in tracking, or in the relationships between changes of these indices over time and changes of skinfolds or skinfold-based body fat.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the present study, however, the tracking of each skinfold and of skinfold-based body fat was correlated to that of BMI, thus not invalidating the use of BMI when analyzing the tracking of adiposity in children. Together with BMI, we analyzed the iBMI, because this index was suggested to be more biologically sound than the BMI and to represent a better proxy of fat mass [33]. However, we observed no substantial difference between BMI and iBMI in tracking, or in the relationships between changes of these indices over time and changes of skinfolds or skinfold-based body fat.…”
Section: Discussionmentioning
confidence: 61%
“…BMI and skinfoldbased body fat were used to analyze how these parameters track over time and to evaluate the relationship between changes occurring in such parameters. Furthermore, we evaluated the inverted BMI (iBMI, expressed in cm 2 /kg) that was recently shown to be a sound alternative to BMI as a proxy for body fatness [33].…”
Section: Introductionmentioning
confidence: 99%
“…These issues influence the diagnostic accuracy of BMI to diagnose overweight/obesity status among adolescents. The issue has been examined in adults [43] and more recently in youth [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Results of multiple regression analyses among Portuguese youth 8–16 years of age suggested that fatness was inversely and significantly related to CRF, whereas sexual maturity status (self-assessed stages of breast development in girls and pubic hair in boys) accounted for only a small portion of the variance in CRF [16]. Before the obesity epidemic, fatness was equally correlated with fat and fat-free mass [17], but more recent studies suggested that fatness was more correlated to BMI in overweight and obese children [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Pediatric-based studies have demonstrated that iBMI is a better predictor of physical activity 8 and resting blood pressure 11 and comparable to BMI in predicting skinfold-determined body fatness. 12 Adult-based work has evidenced that iBMI is a superior proxy for body fat compared with BMI. 1 However, the utility of iBMI as a proxy for body fatness in pediatric samples has not been fully investigated, and research needs to ascertain how iBMI compares to actual fatness using a gold standard measurement technique to provide robust data to support or refute its use as a proxy for adiposity in pediatric samples.…”
Section: Introductionmentioning
confidence: 99%